An Exploratory Study on Olfactory Cues in Retail Stores - Rao, Akshat Aditya; Jain, Bharti (Indian Journal of Marketing, 2021)
The study aimed to explore the factors of olfaction that affected purchases in retail stores and shed light on the enablers of olfactory factors for retailers. The study was accomplished by using structured questionnaires in the urban cities of India. A total of 356 customers were surveyed. The inferential statistics techniques, which included exploratory factors analysis and one-way ANOVA were applied. The study extracted 4Is: Interaction with scent, inhabitants of scent, impelling effect of scent, and intensity of scent as prime factors of olfaction that affected customer purchases in retail stores. The study revealed that frequency of visit, amount spent during a visit, and purpose of visiting a retail store were significant enablers of olfactory factors. Olfactory factors obtained in this research will help retail managers apply olfactory cues in controlled (intensity) and best manner (pleasantness and pairing). The study also contributed to the extant literature by highlighting the significance of olfaction for retail stores.